2018
DOI: 10.1177/0301006618783915
|View full text |Cite
|
Sign up to set email alerts
|

Becoming Familiar With a Newly Encountered Face: Evidence of an Own-Race Advantage

Abstract: Adults' ability to match identity in images of unfamiliar faces is impaired for other- compared with own-race faces; their ability to match identity in images of familiar faces is independent of face race. Exposure to within-person variability in appearance plays a key role in face learning. Past research suggests that children need exposure to higher levels of variability than adults to learn a new face-a difference that has been attributed to experience. We predicted that adults' limited experience with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 43 publications
5
26
0
Order By: Relevance
“…These findings suggest an own-race advantage in identity learning from multiple, highly variable images (see also Hayward et al, 2017;Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…These findings suggest an own-race advantage in identity learning from multiple, highly variable images (see also Hayward et al, 2017;Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…In line with previous findings (e.g., Laurence et al, 2016), we expected better sorting of own-than other-race identities. Based on recent findings that other-race faces are harder to learn than own-race faces (e.g., Zhou et al, 2018), we also expected overall better matching accuracy with own-race faces and a stronger performance increase over blocks for this face category. With respect to ERPs, we expected to replicate the findings of Andrews et al 2017for own-race faces.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In this study, a name identification test with new images of the learnt identities revealed higher accuracies for identifying own-race compared to other-race identities. Similarly, Zhou, Matthews, Baker, and Mondloch (2018) showed an own-race advantage in a paradigm where identities were learnt from a single image, a low variability video, or a high variability video.…”
Section: Learning Own-and Other-race Facial Identities From Natural Vmentioning
confidence: 95%